Meningkatkan Pemahaman Belajar Siswa Fase D Pada Materi Kemampuanku Terbatas Dengan Metode Problem Based Learning Di SMPN 6 Palangka Raya - Isusanti, Sesilia (Jurnal Ilmiah Kanderang Tingang, 2025)
This study aims to improve students' understanding and learning outcomes in Catholic Religion subjects on the topic "My Abilities Are Limited" using the Problem-Based Learning (PBL) method at SMPN 6 Palangka Raya. The research adopts a Classroom Action Research (CAR) design with 15 seventh-grade students from SMPN 6 Palangka Raya in the 2022/2023 academic year as the subjects. The research instruments include observations of student and teacher activities, as well as student learning outcome tests. Assessment was conducted through a written test consisting of 10 multiple-choice questions. Based on the students' learning data from SMPN 6 Palangka Raya in the 2021/2022 academic year for the Catholic Religion subject, 12 out of 15 students had not met the Minimum Mastery Criteria (KKM), while only 6 students achieved the passing score, with an average score of 75.46 (40%). In Cycle I, the average student score was 73.33, with 7 students achieving mastery (73.33% classically). In Cycle II, the average score increased to 96.17, where all students achieved mastery (100%). Thus, the results indicate that the PBL method is effective in improving students' understanding and academic achievement.